TILLAGE AND NITROGEN MANAGEMENT EFFECT ON ENERGY EFFICIENCY IN AEROBIC RICE - G , NAVEEN KUMAR; B , SREEDEVI; V, CHANDRIKA (The Journal of Research ANGRAU, 2026)
A field experiment conducted at the Indian Institute of Rice Research, Hyderabad, Telangana, India, during the rabi season (November-April) of 2022 and 2023 assessed the impact of tillage practices and nitrogen fertilizer schedules on energy efficiency in aerobic rice. The study employed three tillage treatments (T) and five nitrogen fertilizer schedules (N) in a strip plot design with three replications. Results revealed that Conventional tillage (T1 ) showed higher energy input, whereas zero tillage (T3 ) showed lower energy input. Higher Gross Energy Output (GEO), Net Energy Output (NEO), Energy Use Efficiency (EUE) and Energy Productivity (EP) obtained under Conventional tillage (T1 ) which is statistically comparable with minimum tillage with residue retention (T2 ) and significantly higher over zero tillage (T3 ). Zero tillage (T3 ) resulted in the highest energy intensity in physical terms (EIP). Energy Intensity in Economic terms (EIE) was not significantly influenced by tillage practices. Among nitrogen fertilizer schedules, the treatment 100% RDN + foliar spray of 2.5 ml l-1 nano urea at tillering and before panicle initiation stage (N2 ) yielded the highest energy metrics, including GEO and NEO, EUE, EP and EIP which is statistically comparable to 100% RDN (N1 ). Conventional tillage (T1 ) and 100% RDN (N1 ) treatment demonstrated superior performance across various energetics, emphasizing their effectiveness in enhancing the energetic efficiency of aerobic rice cultivation. Overall, conventional tillage and recommended nitrogen management were most effective, while conservation tillage performed on par with conventional tillage in aerobic rice.